A mater of loss - Phoebus Osborne (Performance Philosophy)
How can one imagine speaking to grief using language? How do we hold such a thing within language, imperial language no less? When we centre grief, do we make it generic? When you say grief and I say grief, is it even possible to mean the same thing? What is missing when we say grief, when we gather to contemplate grief, when we claim to research grief? This article explores these and other questions in a multidisciplinary format combining film, images and autobiographical writing.